Paprika Schlesinger: The development of a luxury retail shoe brand in Belle Époque, Vienna. (20th February 2017) - Hawkins, Richard A.
Abstract : Purpose: This paper explores the development of a luxury retail shoe brand in Belle Époque Vienna. Design/methodology/approach: Footwear retailing and marketing history is a neglected area. Unfortunately, no business records have survived from Robert Schlesinger's shoe stores. However, it has been possible to reconstruct the history of the development of the Paprika Schlesinger brand from its extensive advertising in the Viennese newspaper, the Neue Freie Presse, with the guidance of the founder's grandson, Prof Robert A. Shaw, Emeritus Professor of Chemistry, Birkbeck, University of London, England. This case study would not have been possible without the digitization of some major collections of primary sources. In 2014, the European Union's Europeana digitization initiative launched a new portal via the Library of Europe website which provides access to selected digitized historic newspaper collections in libraries across Europe. The project partners include the Austrian National Library which has digitized full runs of several major historic Austrian newspapers, including the Neue Freie Presse . Other project partners which have digitized historic newspapers which are relevant to this paper are the Landesbibliothek Dr Friedrich Teßmann of Italy's Südtirol region, the National Library of France and the Berlin State Library. An associate project partner library, the Slovenian National and University Library's Digital Library of Slovenia, has also digitized relevant historic newspapers. Furthermore, the City of Vienna has digitized a complete set of Vienna city directories as part of its Wienbibliothek Digital project. Findings: This paper suggests that Robert Schlesinger created one of the first European luxury retail shoe brands. Originality/value: This is the first academic study of the historical development of the advertising and marketing of a European luxury retail shoe brand.